International security management and the United Nations - "Inoguchi, Takashi. (ed.)" (New Delhi, 2004)
What kind of comparative advantage does the United Nations hold in the field of security compared to other actors such as states and regional organizations? What kind of asset does the United Nations have in terms of normative as well as operational capacities that states and regional arrangements lack? What asset does the United Nations possess to effectively deal with security issues? These are some of the questions addressed in this book. Obviously, the ability of the United Nations to ease conflicts depends upon the support of Member States. Therefore it is imperative to know what states expect from the world body. As a result, this book also explores the following questions: What is the vision of the Member States and specifically of the major powers? What kind of vision do states have for the United Nations in the field of security? How can the United Nations minimize the volatility and even reluctance of Member States support in the field of security? How is it possible to organize and secure a real and effective partnership between the United Nations and Member States regarding conflict prevention and conflict management? At a time when security issues are changing and becoming increasingly complex to address, this will prove to be very useful for students and practitioners of international affairs.
Keywords: National security